Implementation of Brizzi as an E-Money Payment Tools in Indonesia - Asri Elies Alamanda; Tulus Sartono (Universitas Ahmad Dahlan, 2019)
Introduction to The Problem: The rapid technological progress at this time has greatly influenced the development of the payment system in Indonesia. Innovations in electronic payment instruments have developed into more usable forms. Currently, like the other country, Indonesia is developing an electronic payment instrument known this day as e-money. Bank Rakyat Indonesia is one of the e-money issuer institutions, which issues Brizzi as an alternative non-cash payment instrument. The problem faced is that there are still many people who do not want to use e-money, especially Brizzi because they do not know the validity of using Brizzi e-money.Purpose/Objective Study: This research aims to study the importance of Brizzi E-Money as a means of payment.Design/Methodology/Approach: This research uses empirical juridical research methods to answer the validity of using Brizzi e-money as a payment method. This study uses primary data and secondary data. The primary data in this research are obtained from interviews at Bank Rakyat Indonesia, Merlung Branch. Other than that is secondary data collected through library research.Findings: This research shows that the existence of e-money continues to experience significant development from 2009 until 2019. The legality of using Brizzi e-money and other e-money in Indonesia has been recognized as a legal payment instrument as regulated in the PBI on Electronic Money.Paper Type: Research Article.